British and Austrian documents for the position of the Muslim population in Salonica and its surrounding area during the Balkan Wars - Goseva, Vera; Kotlar-Traykova, Natasha (Balcanica Posnaniensia. Acta et studia, 2012)
In the article we shall study the position of the second largest community in the city of Salonica – the Muslim community – during the Balkan Wars (1912-1913), using British and Austrian documents. We can conclude that the Balkan Wars satisfied the ambitions of the Balkan states’ nationalist circles which, of course, had the politics of the Great Powers behind them. That such of the case was obvious at both conferences that took place in London at the same time – the Conference of the Ambassadors of the Great Powers and the Peace Conference of the Balkan states engaged in war. 80 years after these wars, a new war threatened the Balkans and was led, with all its attributes of cruelty, on the territory of former Yugoslavia. Reflecting on this phenomenon from today’s perspective, we can come to the conclusion that the historical lesson taught by the Balkan Wars (1912/13) had not been learnt.